Real-world cost-effectiveness analysis of thymoglobulin versus no induction therapy in kidney transplant recipients at low risk of graft loss - Adrieli Barros Bessa; Marina Pontello Cristelli; Claudia Rosso Felipe; Renato Demarchi Foresto; Marcelo Cunio Machado Fonseca; Jose Medina Pestana; Helio Tedesco-Silva (Brazilian Journal of Nephrology)
Abstract Background: A new induction therapy strategy of a single 3 mg/kg dose of rabbit antithymocyte globulin (r-ATG) showed a lower incidence of acute rejection. Methods: The objective of this study was to use real-world data to determine the incremental cost-effectiveness ratio (ICER) of r-ATG induction for the prevention of acute rejection (AR) in the first year following kidney transplantation and for kidney graft survival over 1, 4, and 10 years of post-transplantation from the perspective of the national public healthcare system. A Markov state transition model was developed utilizing real-world data extracted from medical invoices from a single center. The study population consisted of adults at low immunological risk undergoing their initial transplantation and received kidneys from either living or deceased donors. The intervention of r-ATG induction was compared to no induction. The clinical outcomes considered for this analysis were acute rejection, cytomegalovirus infection/disease, death, graft loss, and retransplantation. Results: The cost-effectiveness analysis in the first year revealed that the r-ATG group was more cost-effective, with an ICER of US$ 399.96 per avoided AR episode, an effectiveness gain of 0.01 year in graft survival and a total incremental cost of US$ 147.50. The 4- and 10-year analyses revealed an effectiveness gain of 0.06 and 0.16 years in graft survival in the r-ATG induction group, and a total incremental cost of US$ −321.68 and US$ −2,440.62, respectively. Conclusion: The single 3 mg/kg dose of r-ATG is cost-effective in preventing acute rejection episodes and dominant in the long term of transplantation, conferring survival gain.